Yemeni EFL students’ perceptions and implementation of computer-assisted language learning. - Sabri Thabit Saleh Ahmed; Bushra Thabit Ahmed Salem; Sunil V. Pawar (University of Kuningan, 2020)
: This study investigated how Yemeni EFL students perceive computer-assisted language learning, the extent to which CALL is implemented in their learning of English in and outside their faculties and the difficulties they encounter when implementing CALL. Data were collected through a questionnaire that targeted 74 Yemeni EFL students and then analyzed by using SPSS 21st version. Results revealed that the students who participated in this study perceive CALL positively (overall mean = 4.1144 out of 5) and believe in its effectiveness in developing their language skills and making their EFL learning enjoyable and interesting. Moreover, Female students showed a higher overall positive attitude towards CALL as compared to their male counterparts and that was reflected in their implementation of CALL too. A significant correlation was also found between students’ perceptions of CALL and their computer competence in the favor of those students with higher computer competence while no significant correlation was found in relation to age. The results have also revealed that CALL’s implementation by many of the participants is still low. Unavailability of internet and lack of CALL tools at their faculty; in addition to students’ lack of computer competence are viewed as the major barriers to CALL implementation by the Yemeni EFL students understudy. As per the results, the study recommends Yemeni Universities to provide CALL tools and internet for their EFL classrooms and libraries and to train students to use technology for English learning purposes. It also recommends Yemeni EFL students to invest technology at hand for their EFL learning.